Las quemas agrícolas domésticas y su incidencia en la ley de gestión ambiental - Zambrano Cedeño, Héctor Enrique (2014)
You burn them agricultural and their incidence in the Law of Environmental Administration, you to present the proposal of artificial reformation to the art. 246 of the Code Organic Penal Integral in the related to crimes against the biodiversity, considering the you burn agricultural or maidservants carried out by the communities or small farmers inside their territory like punishable facts, worthy of sanction. The thesis understands six chapters: The I chapter, is carried out the analysis juridical partner for the problem confirmation of Hypothesis closely linked with the problem all these previously established ones inside the thesis project. The II chapter, by means of the conceptualization, doctrine, definition, juridical analysis and compared legislation. In the III chapter, the methodology used for me the investigation; as the applied methods, the investigation types, the population, the samples the techniques and instruments used in the gathering of required data. In IV chapter, in the field investigation it is developed the resources fully verifiable with the development and analysis and interpretation of the surveys, made several lawyers in free professional exercise that you/they know like they are the rights of the citizens on the part of those who are devoted to you burn them agricultural domestic without taking into account the laws that you/they take care of the environment that which allows me to sustain in affirmative form the Hypothesis of my investigation. The V chapter, is based my of investigation with the conclusions and recommendations. Finally the sixth chapter speaks of the Proposal, the beneficiaries and of the social impact